The Feasibility of Using Tartary Buckwheat as a Se-Containing Food Material - Aleksandra Golob; Vekoslava Stibilj; Ivan Kreft; Mateja Germ (Journal of Chemistry)
Tartary buckwheat (Fagopyrum tataricum) is a semiwild plant grown in the Himalaya region. Due to its high concentration of flavonoids and trace elements it is of interest for cultivation in other countries as well. The feasibility of increasing the concentration of Se in grain and in green parts of Tartary buckwheat has not yet been investigated. The aim of this investigation was thus to determine the concentration of Se in different edible parts of Tartary buckwheat treated with different concentrations of Na selenate using different techniques. In plants grown in soil fertilized once with 0.5 and 10 mg Se L−1, Se was efficiently translocated from the roots to the leaves and seeds. Foliar spraying with 0.5 mg Se L−1 increased Se content in leaves and seeds. Among the edible parts of Tartary buckwheat plants the highest content of Se in control and in treated groups was found in leaves, followed by seeds and stems. Regarding recommended Se concentration, edible parts of Tartary buckwheat were safe for human consumption. Soil fertilization with 0.5 and 10 mg Se L−1 and foliar fertilization with 0.5 mg Se L−1 are applicable for cultivation of Tartary buckwheat as a functional food enriched with Se.